UMPSA achieves outstanding success at DICE 3.0, sets records in Malaysia Book of Records - Naqiah, Puaad (UMPSA, 2025)
JOHOR BAHRU, 3 September 2025 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) was once again elevated at the international level when two teams from the Faculty of Computing achieved outstanding success in the Digital Innovation Creativepreneur Programme 3.0 (DICE 3.0) held at Persada Johor International Convention Centre, Johor Bahru.